PERAN INOVASI PRODUK DALAM MEMEDIASI DIGITAL MARKETING TERHADAP KINERJA PEMASARAN PADA PELAKU USAHA MEBEL DI DESA LEILEM KABUPATEN MINAHASA - Raintung, Michael Ch.; Kawet, Raymond C.; Mandagie, Yunita (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The furniture industry in Leilem village, Minahasa Regency is one of the industries that continues to grow, business actors are required to be able to make the right marketing strategy to maintain the survival of their business. Digital Marketing is currently one of the tools to market products that are most in demand by business people to promote their business while product innovation is a sustainable market strategy as needed to maintain Marketing Performance. The purpose of this study is to determine the effect of Digital marketing on marketing performance and test whether the Product Innovation variable plays a mediating role in the relationship. The population in this study was 126 furniture craftsmen using the purposive sampling method obtained a sample of 70 respondents. Data collection techniques use data with questionnaires. Instrument testing in this study was carried out based on validity tests and reliability tests and analyzed using path analysis. The results showed partially the variables of Digital Marketing and product Innovation had a positive and significant effect on Marketing Performance, and by using the Sobel test, it can be known that the variable of Product Innovation can mediate the influence of Digital Marketing on Marketing Performance. Keywords: Digital marketing. Product innovation, marketing performance